Konsentrasi Paraquat dalam Urin Pekerja Akibat Paparan Paraquat di Perkebunan Kelapa Sawit - Maksuk - Maksuk (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Paraquat is an active ingredient of herbicide, it is very toxic mainly in humans and can enter the bodythrough ingestion, inhalation and skin. This study aimed to analyze paraquat exposure to paraquat concentrationsin the urine of workers on palm oil plantations. This study used a cross sectional design, with a sample of 60workers and randomly selected, urine was collected on the last day of paraquat spraying. Paraquat in urine wastested in a laboratory using High Performance Liquid Chromatography (HPLC) using the EPA 549.2 methods.Data were analyzed by univariate and bivariate using Mann Whitney test.The average of paraquat concentrationin urine of men workers was 6.35 mg / L and women 6.55 mg / L, with a range between <0.25 - 35.75 mg / L. Theresults of Mann Whitney test showed that the difference of paraquat concentration in urine of workers was influencedby several variables, namely length of work (p=0.026), spraying method (p=0.048), eating / drinking duringapplication (p=0.040), completeness of using personal protection equipment (p=0.03) and decontamination afterspraying (p=0.026).This study provided evidence of paraquat presence in urine workers’. Therefore it is necessaryto urine examination periodically.